Penanganan Konflik Sosial Dengan Pendekatan Keadilan Restoratif - Sukardi, - (UI Scholars Hub, 2016)
Restorative Justice approach in conflict resolution is basically a new method of settling disputes, especially in the concept-criminal cases, but using traditional patterns whose values have no concept of local wisdom in each culture. Therefore, the application of restorative justice approach in conflict resolution, in fact is the use of traditional patterns with the values of the resolution of the existing conflicts in wisdom local culture, with a focus on fulfillment of justice victims, through the concept of equality, partnership, reconciliation and participation.